Towards an atlas of italic types used in Spain, 1528-1700. - Cruickshank, Don (Bulletin of Spanish Studies: Hispanic Studies & Researches on Spain, Portugal & Latin America)
The article discusses the typographical atlas of Spain from 1528-1700. The existence of catalogues with printer indexes, or of comprehensive bibliographies like Norton, have made it possible to produce a dictionary of Spanish printers from the incunabular period to the end of the seventeenth century. printing and the book trade in Spain were affected by economic as well as legal considerations: the latter included the Inquisition and the ban on the printing of plays and novels in Castile (1625-1634); the former, inflation and the government's financial crises. The sixteenth century was the great age of italic type design, and virtually all of the designs listed were produced then, although the most successful ones remained in use well into the eighteenth century.